Lymphoma and Lymphomagenesis in Primary Sjögren’s Syndrome - Alunno, Alessia; Leone, Maria Comasia; Giacomelli, Roberto; Gerli, Roberto; Carubbi, Francesco (Frontiers in Medicine, 2018)
Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disease mainly affecting exocrine glands and leading to impaired secretory function. The clinical picture is dominated by signs and symptoms of mucosal dryness and the course of the disease is mild and indolent in the majority of cases. However, a subgroup of patients can also experience extraglandular manifestations that worsen the disease prognosis. pSS patients are consistently found to have a higher risk of developing non-Hodgkin lymphoma (NHL) compared with patients with other autimmune disorders and to the general population. NHL is the most severe comorbidity that can occur in pSS, therefore recent research has aimed to identify reliable clinical, serological, and histological biomarkers able to predict NHL development in these subjects. This review article encompasses the body of evidence published so far in this field highlighting the challenges and pitfalls of different biomarkers within clinical practice. We also provide an overview of epidemiological data, diagnostic procedures, and evidence-based treatment strategies for NHL in pSS.